6(7u-u)+u=36+u

Simple and best practice solution for 6(7u-u)+u=36+u equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6(7u-u)+u=36+u equation:


Simplifying
6(7u + -1u) + u = 36 + u

Combine like terms: 7u + -1u = 6u
6(6u) + u = 36 + u

Remove parenthesis around (6u)
6 * 6u + u = 36 + u

Multiply 6 * 6
36u + u = 36 + u

Combine like terms: 36u + u = 37u
37u = 36 + u

Solving
37u = 36 + u

Solving for variable 'u'.

Move all terms containing u to the left, all other terms to the right.

Add '-1u' to each side of the equation.
37u + -1u = 36 + u + -1u

Combine like terms: 37u + -1u = 36u
36u = 36 + u + -1u

Combine like terms: u + -1u = 0
36u = 36 + 0
36u = 36

Divide each side by '36'.
u = 1

Simplifying
u = 1

See similar equations:

| 3(4z-2)=2Z-36 | | 3+4z+9=31 | | 8(y+6)=128 | | 3(2x-5)+4(x+2)=-7 | | x^5-2x^4-8x^3=0 | | 2(x+4)=38-4x | | 6v+32=-6+8(v+4) | | -5/8=g-1/4 | | 0.6x=28.3 | | -6(4n-6)-2n=-7n+17 | | y-4=6 | | h+4/9=7/9 | | 7.4+d=-18.62 | | m-9.78=65.32 | | 6.3+k=12.5 | | b/4+10=13 | | 16+2a=-2(3a-4) | | 11-4x=6+x | | 4c+0=48 | | 3g-1+2g+8=g+2 | | A=5i+7j | | u+6=v | | -5+3x+3+2= | | -2(7-4)+4=-4 | | 7a=15a-80 | | 15y-12y=24 | | 0.02=100 | | 20y^7v^8u^2= | | 3(-2+x)=-24 | | 2b-6-3b-b= | | 10+7x=5x-6 | | (2x-1)(x+3)=(x-3)(x+1) |

Equations solver categories